HISTORY OF THE DEVELOPMENT OF SCIENCE - Widya Khairunnisah; Salminawati Salminawati; Rana Farras Irmi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
The type of research that the author uses is a type of qualitative research using a content analysis approach (Content Analysis), or what can be called a content study. This analysis is a research technique for making a conclusion or inference that can be replicated and the correctness of the data by taking into account the context. The object of this research is explored through various information in the form of books, interpretations, journals. The history of science, which is a long process of growth and development of science itself, cannot be separated from its existence. Something brand-new with characteristics specific to that era emerges at each stage of the development of science. The social dynamics of a cultural conflict have led to these characteristics. Obviously, this can't be isolated from different social, social and political impacts that create alongside the advancement of science itself. Thus, the ancient Greek, Islamic, Renaissance, Modern, and Contemporary periods the ancient Greek period, the Islamic period, and the Renaissance and Modern Period can be used to categorize the development of science.